Semi-active control of an experimental frame using MR dampers: numerical results and experimental validation - Braz-César, M.T. (2014)
The present work describes part of the R& D on using a semi-active structural con- trol technique in a civil engineering experim ental model frame equipped with a MR damper, developed within COVICOCEPAD project approved in the framework of Eurocores program S3T. Some results are provided as sociated with the calibration of a magneto-rheological (MR) damper at FEUP (Faculdade de Engenharia da Un iversidade do Porto) as well as on the ex- perimental modal identification of the dynamic properties of a small-scale metallic frame, with and without the inclusion of a specific MR device. Some numerical results of the con- trolled frame under simulated earthquakes are gi ven, to be later compared with the experi- mental results of such frame inst alled in a Quanser shaking table.